Preliminar study on poliphenolic contents and antioxidant capacity of Malus domestica cultivated in Costa Rica - Navarro-Hoyos, Mirtha (2017)
Species such as high altitude fruits, such as Malus domestica have been introduced in Costa Rica and adapted to its climatic conditions, being cultivated specifically in Los Santos region. These efforts have allowed to obtain fruits that are well accepted in the market because of their flavor, aroma and easiness of handling. On the other hand, the advancement of biologic and chemical techniques have enabled more detailed research on polyphenols –abundant in these fruits- because of their bioactive properties such as antioxidant potential. This scientific knowledge has in turn been an important factor in a higher consumption of fruits with high polyphenolic contents both fresh and in nutritional supplements. Hence, the present work focuses in the study of these high altitude fruits cultivated in Costa Rica, regarding agro-ecologic improvement as well as determination of polyphenolic contents and antioxidant capacity. Two cultivars of Malus domestica were acquired, namely Ana and Jonas, which were processed to carry out analyses. Also, work was performed in agro-ecologic conditions amelioration and biocontrol for soil protection. This publication includes preliminary data because of the relevance of the scientific results published for the first time for this economic important species cultivated in Costa Rica.